THE EFFECTIVENESS OF MODERN PEDAGOGICAL TECHNOLOGIES - Bozorova Adiba Khudayarovna (International Scientific and Current Research Conferences, 2025)
This thesis examines the potential of modern pedagogical technologies to revolutionize teaching and learning processes in contemporary education. Drawing from constructivist and social learning theories, it highlights how advanced digital tools can promote active, collaborative, and student-centered instruction. By enabling personalized learning paths and real-time performance tracking, these technologies cater to diverse learner needs and foster motivation. Engaging resources—such as gamified quizzes and virtual reality simulations—enhance students’ understanding of complex concepts.